ANALISIS RASIO RENTABILITAS (STUDI KASUS LAPORAN KEUANGAN PADA PT. BANK MEGA TAHUN 2017-2022) - Cinta Billytona; Moh Rizal, Bayu Aji Laksono, Renny Oktafia (CV. Adiba Aisha Amira, 2024)
Banking plays an important role as a tool to support the growth of a country's economy, including in Indonesia. Bank Mega, one of the national private banks, has a strategic role in the Indonesian banking sector. This study analyzes Bank Mega's financial reports from 2017 to 2022, focusing on profitability ratios: Return on Assets (ROA), Return on Equity (ROE), and Net Interest Margin (NIM). This analysis aims to understand bank financial performance before and during the COVID-19 pandemic. The results show an increase in ROA and ROE from year to year, indicating efficiency in the use of assets and the bank's ability to generate profits from its capital. Meanwhile, NIM remained stable, showing the bank's success in maintaining the efficiency of interest operations. This study provides important insights regarding banks' financial responses and performance in facing complex economic challenges.